Alternative futures for world cereal and meat consumption - Rosegrant, Mark W.; Leach, Nancy; Gerpacio, Roberta V. (Cambridge University Press, 1999)
Fundamental changes in the global structure of food demand will lead to an extra-ordinary increase in the importance of developing countries in global food markets. Economic growth in developing countries is changing consumption patterns, with slower growth (and in many countries actual declines) in per capita food consumption of grains and rapidly growing per capita and total meat consumption, combined with induced growth in cereal feed consumption. The present paper examines the hypothesis, suggested by some researchers, that high-meat diets in developed countries limit improvement in food security in developing countries. These analysts argue that reduced meat consumption in developed countries would release cereals from livestock feed to food for poorer populations, thus improving food security in developing countries. Using the International Food Policy Research Institute (Washington, DC, USA) global food projections model, the international model for policy analysis of agricultural com-modities and trade (see Rosegrant et al. 1995), we first analyse the implications for future global cereal and meat supply and demand resulting from changes in global income, population growth and other structural changes, then simulate alternative sce-narios to examine the effect of large reductions in meat consumption in developed coun-tries on food consumption and food security in developing countries. The paper shows that while the long-term prospects for food supply, demand and trade indicate a strength-ening of world cereal and livestock markets, the improvement in food security in the developing world will be slow, and changes in the dietary patterns in developed countries are not an effective route to improvement in food security in developing countries.